The Influence of Work Motivation Work Discipline Work Environment and Job Satisfaction on Employee Performance at PT. Pos Indonesia (Persero) Pematangsiantar - Fajar Suryani Manurung; Sarida Sirait; Calen (Journal of Management and Business Analytics, 2026)
Employee performance is a crucial factor in determining a company's success in achieving its goals. Every company expects its employees to perform well, thus requiring work motivation, discipline, a supportive work environment, and job satisfaction. This study aims to determine and analyze the influence of work motivation, discipline, the work environment, and job satisfaction on employee performance at PT. Pos Indonesia (Persero) Pematangsiantar. This study used a quantitative approach with descriptive methods. The study population was all 46 employees of PT. Pos Indonesia (Persero) Pematangsiantar, representing 46 respondents working across all divisions within the company. Data analysis was performed using multiple linear regression using SPSS 22. The results indicate that work motivation has a positive and significant effect on employee performance, work discipline has a positive and no significant effect on employee performance, the work environment has a negative but significant effect on employee performance, and job satisfaction has a positive and significant effect on employee performance. Simultaneously, work motivation, discipline, the work environment, and job satisfaction have a significant effect on employee performance at PT. Pos Indonesia (Persero) Pematangsiantar.